Using on-farm sedimentation ponds to improve microbial quality of irrigation water in urban vegetable farming in Ghana - Keraita, Bernard N.; Drechsel, Pay; Konradsen, Flemming (IWA Publishing, 2008)
This paper presents an assessment of the potential of using on-farm ponds to reduce levels of microbial contamination in wastewater -contaminated irrigation water. The study involved observations on the use of ponds in urban agriculture in Kumasi, Ghana, and more than 300 irrigation water samples were taken for physico-chemical and microbial laboratory analysis. The study shows that while on-farm ponds are commonly used, their potential to remove pathogens through sedimentation has not been fully optimized. Two-thirds of helminth eggs were in the sediments and careful collection of irrigation water without disturbing sediments reduced helminth eggs in irrigation water by about 70%. Helminth eggs reduced from about 5 to less than 1 egg per litre in three days in both dry and wet seasons while thermotolerant coliforms took six days in the dry season to reduce from about 8 to 4 log units per 100 ml, to meet the WHO guidelines. For optimal pathogen removal, better pond designs, farmers’ training on collection of water with minimal disturbance and any other means to enhance sedimentation and pathogen die-off can be essential components of a multiple-barrier approach complementing farm-based measures like simple filtration techniques, better irrigation methods and post-harvest contamination.